J Mood Disord Ther 2019
DOI: 10.36959/418/577
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Anxiety during Pregnancy: The Influence of Maternal Characteristics

Abstract: Introduction: Depression and anxiety during pregnancy are associated with adverse health outcomes for both mother and child. This study aimed to investigate the occurrence of symptoms of depression and anxiety in early and late pregnancy, the longitudinal changes from early to late pregnancy, and factors associated with symptoms of depression and anxiety in pregnant women in the Netherlands. Methods: We studied 2897 women participating in the PRegnancy and Infant DEvelopment (PRIDE) Study. To assess symptoms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 69 publications
1
7
0
1
Order By: Relevance
“…Pregnancy-related factors (e.g. unplanned pregnancy and outcomes of pregnancy) were found to be associated with elevated maternal depression in general maternal women, which were dominant risk factors for suicide attempts in women [17][18][19]. However, the relationships between these factors and suicide attempts among women with adolescent pregnancy have been less studied.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy-related factors (e.g. unplanned pregnancy and outcomes of pregnancy) were found to be associated with elevated maternal depression in general maternal women, which were dominant risk factors for suicide attempts in women [17][18][19]. However, the relationships between these factors and suicide attempts among women with adolescent pregnancy have been less studied.…”
Section: Introductionmentioning
confidence: 99%
“…12 In one study, symptoms of anxiety appeared to decrease over the course of pregnancy (from the first to third trimesters 17.9% to 14.2%). 13 A medically high-risk pregnancy is defined as "any pregnancy in which there is evidence of actual or potential threat of harm to the life or health of the mother and/or the baby, because of a disorder or situation coincidental with or unique to pregnancy." 14 Health conditions that lead to increased risk can be obstetrical (eg, placenta previa), maternal (eg, preeclampsia), and/or fetal (eg, prematurity).…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in South African showed that the prevalence of prenatal depression was 21% [ 46 ]. The prevalence of prenatal depression was 27.5% among Turkish Women [ 47 ], 10.0% during late pregnancy in the Netherlands [ 48 ], 14.8% in Spain [ 49 ], and 6.1% in the US [ 50 ]. These results also indicate that there are differences in the prevalence of prenatal depression among pregnant women from different cultures.…”
Section: Discussionmentioning
confidence: 99%